Unveiling Practitioners Awareness of Android Apps Regression Testing through an Expert Survey - Lima, Sara Mendes Oliveira; Campos, Denivan; Soares, Larissa Rocha; Machado, Ivan (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
The mobile device market is continuously growing. Delivering apps with quality, on time, and at a low cost is essential for any company. The development process of apps involves continuous maintenance, which leads to an ever-increasing number of updates. Thus, strategies for producing quality, easy-to-maintain applications are essential. In this context, software testing plays a particularly important role, in particular regression testing strategies, which are aimed at ensuring the quality of an app after maintenance. Regression testing checks whether the application's functional behavior has not being compromised after a software update. The literature presents many studies and tools on regression testing techniques to reduce the number of tests to be re-executed during the maintenance and evolution. However, as far as we know, the community is unaware of which ones are actually used in Android development practice. In this sense, this study investigates how testers and developers perform regression testing on Android applications. From a survey with 100 participants, we found that the testing of Android applications is performed mainly manually and without the support of tools. The yielded results bring initial insights about the current scenario of regression testing in Android apps development and show the importance of the relationship between research and market, which may bring several opportunities for future researches.